PENERAPAN MODEL DISCOVERY LEARNING (DL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.2 SMP NEGERI 8 PEKANBARU - Lidya Ika Rahamadalena; Jalinus Jalinus; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on mathematics learning achievement on Circle topic of students VIII.2 of Junior High School 8 Pekanbaru which shows that 28 of 40 students still have scores which stand under KKM that has been settled by the school that is 78. This research aims to improve learning process and students’ mathematics learning achievement by applying Discovery Learning (DL) model. This research is a classroom action research with two cycles. The research instruments used are mathematical learning instruments and data collecting instruments. The mathematical learning instruments are Syllabus, Lesson Plans, and Activity Sheets. The data collecting instruments are Observation Sheets and Students Mathematic Tests. Analysis techniques that used are descriptive narrative on qualitative data and descriptive statistics on quantitative data. Subject of this research are students of VIII.2 Junior High School 8 Pekanbaru in second semester of academic year 2017/2018, which consist of 16 males and 24 females with heterogeneous abilities. Based on the analysis of students and teacher activities after implementation of the DL model, it can be concluded that there is an improvement of learning process. On knowledge competence, in Cycle I with percentage 37,5% and 42,5% in Cycle II. On skill competence, the number of students who can reach KKM in Cycle I with percentage 62,5% and 67,5% in Cycle II. Based on the result, it can be concluded that the implementation of DL model can improve the learning process and the students’ mathematics learning outcomes at class VIII.2 of Junior High School 8 Pekanbaru.Key Words : Mathematics Learning Achievement, Discovery Learning Model, Classroom Action Research